International Quality-Controlled Ocean Database (IQuOD) v0.1: The Temperature Uncertainty Specification - Cowley, Rebecca; Killick, Rachel E.; Boyer, Tim; Gouretski, Viktor; Reseghetti, Franco; Kizu, Shoichi; Palmer, Matthew D.; Cheng, Lijing; Storto, Andrea; Le Menn, Marc; Simoncelli, Simona; Macdonald, Alison M.; et al. (Frontiers in Marine Science, 2021)
Ocean temperature observations are crucial for a host of climate research and forecasting activities, such as climate monitoring, ocean reanalysis and state estimation, seasonal-to-decadal forecasts, and ocean forecasting. For all of these applications, it is crucial to understand the uncertainty attached to each of the observations, accounting for changes in instrument technology and observing practices over time. Here, we describe the rationale behind the uncertainty specification provided for all in situ ocean temperature observations in the International Quality-controlled Ocean Database (IQuOD) v0.1, a value-added data product served alongside the World Ocean Database (WOD). We collected information from manufacturer specifications and other publications, providing the end user with uncertainty estimates based mainly on instrument type, along with extant auxiliary information such as calibration and collection method. The provision of a consistent set of observation uncertainties will provide a more complete understanding of historical ocean observations used to examine the changing environment. Moving forward, IQuOD will continue to work with the ocean observation, data assimilation and ocean climate communities to further refine uncertainty quantification. We encourage submissions of metadata and information about historical practices to the IQuOD project and WOD.